Construction and validation of an instrument to identify barriers to implementing pharmaceutical care - Luanna Gabriella Resende da Silva; Rúbia Yumi Murakami Silva; Mariana Linhares Pereira; Maria Teresa Herdeiro; André Oliveira Baldoni (Exploratory Research in Clinical and Social Pharmacy)
Background: Pharmaceutical Care is a professional practice in high demand for implementation in Primary Health Care within the Public Health System. Consequently, it was necessary to develop and validate an instrument to assess the obstacles to this process. Methods: A methodological study was conducted in three stages: first, the questionnaire was developed based on the APOTECA framework, which includes Attitudinal, Political, Technical, and Administrative domains. Second, the content was validated using the Delphi Technique, with a content validity coefficient greater than or equal to 0.8 considered acceptable. Third, a pre-test was conducted with pharmacists working in Primary Health Care within the Public Health System. After validation, the instrument was administered to pharmacists participating in a training and support project for the implementation of Pharmaceutical Care. Results: The results indicated that the instrument was validated after two rounds of evaluation, with the first round involving 33 experts achieving a total content validity coefficient of 96 %, and the second round involving 18 experts achieving a total content validity coefficient of 98 %. In the third stage, the pre-test with Primary Health Care pharmacists resulted in a total content validity coefficient of 91 %. The final version of the questionnaire, which incorporated suggestions for improvements, included 19 questions. When answered by pharmacists, the responses indicated that Technical questions were the most significant barrier to implementation, followed by Political, Attitudinal, and Administrative questions. Conclusion: The validation of this instrument provides an important tool for identifying factors that hinder the implementation of Pharmaceutical Care within the Public Health System.